Audiovisual Temporal Perception in Aging: The Role of Multisensory Integration and Age-Related Sensory Loss - Brooks, Cassandra J.; Chan, Yu Man; Anderson, Andrew J.; McKendrick, Allison M. (Frontiers in Human Neuroscience, 2018)
Within each sensory modality, age-related deficits in temporal perception contribute to the difficulties older adults experience when performing everyday tasks. Since perceptual experience is inherently multisensory, older adults also face the added challenge of appropriately integrating or segregating the auditory and visual cues present in our dynamic environment into coherent representations of distinct objects. As such, many studies have investigated how older adults perform when integrating temporal information across audition and vision. This review covers both direct judgements about temporal information (the sound‐induced flash illusion, temporal order, perceived synchrony and temporal rate discrimination) and judgements regarding stimuli containing temporal information (the audiovisual bounce effect and speech perception). Although an age-related increase in integration has been demonstrated on a variety of tasks, research specifically investigating the ability of older adults to integrate temporal auditory and visual cues has produced disparate results. In this short review, we explore what factors could underlie these divergent findings. We conclude that both task-specific differences and age-related sensory loss play a role in the reported disparity in age-related effects on the integration of auditory and visual temporal information.